Answer:
• 3y+x=13
,
• y+3x=7
,
• y-x=3
Step-by-step explanation:
Given points A(4,3), B(0,7), C(-1,2):
First, we find the coordinates of the midpoints of AB, AC and BC.
![\begin{gathered} \text{Midpoint of AB}=\mleft((4+0)/(2),(3+7)/(2)\mright)=(2,5) \\ \text{Midpoint of AC}=\mleft((4-1)/(2),(3+2)/(2)\mright)=(1.5,2.5) \\ \text{Midpoint of BC}=\mleft((0-1)/(2),(7+2)/(2)\mright)=(-0.5,4.5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jhypcgspfetocgtygjly460oiwusq3vs4r.png)
Part 1
The equation of the median from A to BC.
Using points: A(4,3) and (-0.5,4.5) in the two-point form, we have:
![\begin{gathered} (y-y_1)/(x-x_1)=(y_2-y_1)/(x_2-x_1) \\ (y-3)/(x-4)=(4.5-3)/(-0.5-4) \\ (y-3)/(x-4)=(1.5)/(-4.5) \\ (y-3)/(x-4)=-(1)/(3) \\ 3(y-3)=-1(x-4) \\ 3y-9=-x+4 \\ 3y+x=4+9 \\ 3y+x=13 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k3s6n4tmdb0grrjt41cf5844abl3bwkvtv.png)
Part 2
The equation of the median from B to AC.
Using points: B(0,7) and (1.5,2.5) in the two-point form, we have:
![\begin{gathered} (y-y_1)/(x-x_1)=(y_2-y_1)/(x_2-x_1) \\ (y-7)/(x-0)=(2.5-7)/(1.5-0) \\ (y-7)/(x)=(-4.5)/(1.5) \\ (y-7)/(x)=-3 \\ y-7=-3x \\ y+3x=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sxfy1ff9awxn2smcuqrhjhcj9kcjf8tn94.png)
Part 3
The equation of the median from C to AB.
Using points: C(-1,2) and (2,5) in the two-point form, we have:
![\begin{gathered} (y-y_1)/(x-x_1)=(y_2-y_1)/(x_2-x_1) \\ (y-2)/(x+1)=(5-2)/(2+1) \\ (y-2)/(x+1)=(3)/(3) \\ (y-2)/(x+1)=1 \\ y-2=x+1 \\ y-x=1+2 \\ y-x=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/oyi2fi7lny9vtz7s54v4puxjcqcq9gv091.png)
The equations of the medians are:
• 3y+x=13
,
• y+3x=7
,
• y-x=3